Intraoral 3D Scanning or Dental Impressions for the Assessment of Dental Arch Relationships in Cleft Care: Which is Superior?. (September 2016) - Chalmers, E.V.; Mcintyre, G.T.; Wang, W.; Gillgrass, T.; Martin, C.B.; Mossey, P.A.
Objective: This study was undertaken to evaluate intraoral 3D scans for assessing dental arch relationships and obtain patient/parent perceptions of impressions and intraoral 3D scanning. Materials & Methods: Forty-three subjects with nonsyndromic unilateral cleft lip and palate (UCLP) had impressions taken for plaster models. These and the teeth were scanned using the R700 Orthodontic Study Model Scanner and Trios® Digital Impressions Scanner (3Shape A/S, Copenhagen, Denmark) to create indirect and direct digital models. All model formats were scored by three observers on two occasions using the GOSLON and modified Huddart Bodenham (MHB) indices. Participants and parents scored their perceptions of impressions and scanning from 1 (very good) to 5 (very bad). Intra- and interexaminer reliability were tested using GOSLON and MHB data (Cronbach's Alpha >0.9). Bland and Altman plots were created for MHB data, with each model medium (one-sample t tests, P < .05) and questionnaire data (Wilcoxon signed ranks P < .05) tested. Results: Intra- and interexaminer reliability (>0.9) were good for all formats with the direct digital models having the lowest interexaminer differences. Participants had higher ratings for scanning comfort (84.8%) than impressions (44.2%) ( P < .05) and for scanning time (56.6%) than impressions (51.2%) ( P > .05). None disliked scanning, but 16.3% disliked impressions. Data for parents and children positively correlated ( P < .05). Conclusions: Reliability of scoring dental arch relationships using intraoral 3D scans was superior to indirect digital and to plaster models; Subjects with UCLP preferred intra-oral 3D scanning to dental impressions, mirrored by parents/carers; This study supports the replacement of conventional impressions with intra-oral 3D scans in longitudinal evaluations of the outcomes of cleft care.